El nacimiento y ascenso de los civil lawyers - García Long, Sergio (Pontificia Universidad Católica del Perú, 2018)
Civil law has changed. Now, Civil Law has become a European law. Interestingly this European Civil Law has developed in English language.We also must add to the picture the process of globalization of American law. The contract law that is being used by practitioners in corporate and financing deals is based on American contract clauses which are not regulated by civil codes. Many of these deals are written in English language. This new environment of the Civil Law in the international field demands adaption for lawyers if they want to survive in the legal practice.

El derecho civil no es el mismo de antes. Ahora, el derecho civil se ha convertido en un derecho europeo. Lo interesante es que este derecho civil europeo se ha desarrollado en inglés.A ello hay que añadirle la globalización del derecho americano. En la práctica, el derecho contractual que se usa en transacciones corporativas y financieras se basa en cláusulas contractuales americanas que no se encuentran reguladas en los códigos civiles. Incluso muchos de estos contratos se redactan en inglés. Esta nueva realidad del derecho civil en el plano internacional nos exige adaptarnos si es que queremos sobrevivir a la práctica profesional.
The birth and rise of the civil lawyers
Keywords: Civil law; Common law; Derecho comparado; Historia del derecho; Americanización; https://purl.org/pe-repo/ocde/ford#5.05.01